Theoretical foundations and methodology formation of ideal-normative model of a hierarchy of levels of value consciousness (Journal of Philosophy Culture and Political Science, 2018)
Values appear and function as human orientation and preferences in a particular cultural matrix. Besides the fact that the values are historical, dynamic and pluralistic, in a study to consider that they are not mutually exclusive. Conceptual and methodological bases axiology socialization norms from an empirical assessment of the situation allows to demonstrate the importance of targeting of value formation of children and youth to preserve the Kazakh national identity formation and continued satisfactory operation of the rule of law and democratic institutions as a basis for the development of modern states. About the problems of organizing, classifying and determining the methodological significance of values in the social and humanitarian knowledge developed many theories, partly contradictory. In keeping with the search for new interpretations of questions of value orientations should, first of all, note that the new research solutions are constructed by contamination of theoretical approaches, their development, and not eliminate conceptual differences. Key words: person, the philosophical and spiritual values, ideals, needs, norms, structure, axiology.